2020
DOI: 10.1039/c9cp06484b
|View full text |Cite
|
Sign up to set email alerts
|

The quest to uncover the nature of benzonitrile anion

Abstract: Anionic states of benzonitrile are investigated by high-level electronic structure methods.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…This feature was distinguished from the vibrational structure of the valence state by the anisotropy induced by the dipole electric field. More recently, accurate photoelectron spectra of benzonitrile have been analysed by Gulania et al 54 with a high-level electronic structure calculation of its anionic states. This investigation reveals the presence of a dipole-bound state, that provides the main mechanism to capture an incoming electron but leads to the formation of valence anions via non-adiabatic relaxation (see ref.…”
Section: And References Therein)mentioning
confidence: 99%
See 1 more Smart Citation
“…This feature was distinguished from the vibrational structure of the valence state by the anisotropy induced by the dipole electric field. More recently, accurate photoelectron spectra of benzonitrile have been analysed by Gulania et al 54 with a high-level electronic structure calculation of its anionic states. This investigation reveals the presence of a dipole-bound state, that provides the main mechanism to capture an incoming electron but leads to the formation of valence anions via non-adiabatic relaxation (see ref.…”
Section: And References Therein)mentioning
confidence: 99%
“…This investigation reveals the presence of a dipole-bound state, that provides the main mechanism to capture an incoming electron but leads to the formation of valence anions via non-adiabatic relaxation (see ref. 54 and references therein). Interconnections between valence states of anions and dipole-bound states have also been identified in the opposite direction (bifurcation of the excited state wavepacket leading to the formation of a non-valence state) for a common anionic chromophore, 55 and the stability of such orbitals in the presence of perturbing molecules has also been studied by the same group.…”
Section: And References Therein)mentioning
confidence: 99%
“…Aside from DEA, there are anions whose autodetachment is entirely due to nuclear motion, [216][217][218] for example NH − 219 and enolates, 220 as well as other anions that are adiabatically bound only when zero-point vibrational energies are taken into account, for example benzonitrile. 221 Vibrational effects hence play a decisive role for the spectroscopy of temporary anions, 10 but also for other types of resonances such as core-vacant states. 8 Using the Siegert representation, Eq.…”
Section: Recent Methodological Developments 41 Complex-valued Potenti...mentioning
confidence: 99%
“…The extraterrestrial detection of benzonitrile has fostered several laboratory studies. A recent study reported the aromatic CH stretching frequencies of cationic benzonitrile (benzonitrile + ) and the formation of a CH···O-type hydrogen bond (H-bond) with polar water solvents . The same group also reported an exclusive nitrogen protonation of this aromatic moiety and a hydration-induced solute-to-solvent proton transfer that causes switching of the H-bond framework from NH···O to N···HO following the addition of two or more water ligands. , While in the anionic benzonitrile–water complex, the solvent water only forms a nearly linear N···HO H-bond with the negatively charged ring, in case of the neutral benzonitrile–water complex based on gas-phase IR and microwave studies of a cyclic global minimum structure, where the solvent water simultaneously forms a OH···π H-bond with π electrons of the CN group and a CH···O H-bond with the adjacent ortho CH proton donor was proposed. Further addition of water molecules leads to the formation of a H-bonded solvent network that results in the expansion of the cyclic water ring present in the monohydrate.…”
Section: Introductionmentioning
confidence: 99%